2015
DOI: 10.1186/s12885-015-1528-y
|View full text |Cite
|
Sign up to set email alerts
|

The Breast Cancer to Bone (B2B) Metastases Research Program: a multi-disciplinary investigation of bone metastases from breast cancer

Abstract: BackgroundBone is the most common site of breast cancer distant metastasis, affecting 50–70 % of patients who develop metastatic disease. Despite decades of informative research, the effective prevention, prediction and treatment of these lesions remains elusive. The Breast Cancer to Bone (B2B) Metastases Research Program consists of a prospective cohort of incident breast cancer patients and four sub-projects that are investigating priority areas in breast cancer bone metastases. These include the impact of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 105 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…More recently, Hoshino et al , demonstrated that tumour exosome integrins prepare a favourable microenvironment at future metastatic sites and mediate non-random patterns of metastasis [ 29 ]. Thereby BC metastasis organotropism, tumour-microenvironment interactions, and strategies to address them for prevention and treatment of BM are areas of intense investigation [ 30 , 31 ]…”
Section: Pathophysiology Of Breast Cancer Metastasis To the Bonementioning
confidence: 99%
“…More recently, Hoshino et al , demonstrated that tumour exosome integrins prepare a favourable microenvironment at future metastatic sites and mediate non-random patterns of metastasis [ 29 ]. Thereby BC metastasis organotropism, tumour-microenvironment interactions, and strategies to address them for prevention and treatment of BM are areas of intense investigation [ 30 , 31 ]…”
Section: Pathophysiology Of Breast Cancer Metastasis To the Bonementioning
confidence: 99%
“…1 Because hormone receptor–positive breast cancer cells prefer an osseous microenvironment, about 70% of breast cancer metastases are bone recurrences. 2,3 Nitrogen-containing bisphosphonates such as ibandronate affect bone metabolism by inhibiting key enzymes of the intracellular mevalonate pathway. 4 This decreases osteoclast-mediated bone resorption and osteoclast survival, causing an increase in bone density and a decreased release of cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in the treatment of breast cancer, up to 30% of patients still develop distant metastases over the course of the disease [3]. Herein, the skeleton is the most frequent site of distant metastases in breast cancer patients, accounting for 50-70% of all metastases [3][4][5][6][7]. The affection of the bone can cause various complications such as pain, pathological fractures, spinal cord compression, and hypercalcemia, which often have a major impact on patients' morbidity and mortality [8][9][10].…”
Section: Introductionmentioning
confidence: 99%